Development of an Integrated Policy and Support Programme for Micro Rural Food Enterprises in an EU Peripheral Region. (May 2015) - McAdam, Rodney; Quinn, Barry; McKitterick, Lynsey; Dunn, Adele; Patterson, David
This case study explores how a peripheral rural region food support programme for small (micro) food enterprises was developed based on regional government food policy. An exploratory case study methodology is employed. The findings show that integration of policy and practice at a regional level should be reflected in the design and implementation of micro food business support programmes. This integration is essential to enable micro businesses to benefit from government aid in a collective manner which could not be achieved in government–micro-enterprise dyadic relationships.